A Novel Boost-Buck Converter Architecture for Improving Transient Response and Output-Voltage Ripple - Freddy Kurniawan; Lasmadi Lasmadi; Okto Dinaryanto; Bambang Sudibya; Mohammad Ridlo Erdata Nasution (Journal of ICT Research and Applications, 2020)
Buck-boost converters are widely used in the development of DC-DC converters. Several techniques and algorithms have been introduced to improve the transient response of buck-boost converters. However, due to the opposite trends of the output current change and the output voltage change, undershoot or overshoot in the output voltage still seems to be inevitable. In order to overcome this problem, a novel boost-buck converter architecture is proposed to build a fast transient response DC-DC converter. The converter consists of a cascaded configuration of the boost and buck stages. The boost stage converts the input voltage to the shared capacitor voltage and the buck stage supplies energy to the load by converting the shared capacitor voltage to the output voltage. By harnessing the energy stored in the shared capacitor, the transient response of the boost buck converter can be improved to 2 µs in a step-up load current change of 1 A with an output-voltage ripple of 15 mV.